Additively Manufactured Phase-Shifted Antenna Array Model in V-Band - Shi, Jing; Akula, V.; Bachbauer, Felix; Pietschmann, Simon; Maune, H.; Gold, Gerald (2024 54th European Microwave Conference, EuMC 2024, 2024)
A proposed design for a compact liquid crystal (LC) V-Band phased antenna array for inter-satellite links between CubeSats was unveiled, which includes an antenna array, feeding network, and LC phase shifter. In this work, a 4x4 horn antenna array with a corporate feeding network and length varied waveguides as an alternative to LC phase shifter were printed, which was supported with fine detail resolution (FDR) additively manufacturing technology. The phased antenna array was tested at 62.5 GHz with beam steering at 6°, 12°, and 18°, and its gain ranged from 23.79 dB to 18.65 dB in the azimuth plane and from 23.36 dB to 16.65 dB in the elevation plane.
CRIS-Team Scopus Importer:2024-12-13
Keywords: CubeSat; FDR additively manufacturing; feeding network; inter-satellite links; LC phase shifter; phased antenna array; V-Band